1996
DOI: 10.1063/1.472867
|View full text |Cite
|
Sign up to set email alerts
|

Long-range, collision-induced hyperpolarizabilities of atoms or centrosymmetric linear molecules: Theory and numerical results for pairs containing H or He

Abstract: For atoms or molecules of D∞h or higher symmetry, this work gives equations for the long-range, collision-induced changes in the first (Δβ) and second (Δγ) hyperpolarizabilities, complete to order R−7 in the intermolecular separation R for Δβ, and order R−6 for Δγ. The results include nonlinear dipole-induced-dipole (DID) interactions, higher multipole induction, induction due to the nonuniformity of the local fields, back induction, and dispersion. For pairs containing H or He, we have used ab initio values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 104 publications
1
26
0
Order By: Relevance
“…Excellent agreement with the results found by Buckingham et al [14] as well as the results by Hunt [23] and Li et al [12,13] has been found. It is interesting to note that the irreducible Cartesian components can be obtained directly from Cartesian considerations (see Sects.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Excellent agreement with the results found by Buckingham et al [14] as well as the results by Hunt [23] and Li et al [12,13] has been found. It is interesting to note that the irreducible Cartesian components can be obtained directly from Cartesian considerations (see Sects.…”
Section: Resultssupporting
confidence: 81%
“…It has been shown by Buckingham [14], Hunt [23] and Li et al [13], note also [15], that for a pair of atoms A and B the second order correction to the induced first-hyperpolarizability tensor β is given by the following formula (2) For the second order correction to the redundant induced second hyperpolarizability γ we have [14,13]:…”
Section: Second Order Correction To the Redundant First And Second Hymentioning
confidence: 99%
See 1 more Smart Citation
“…(9) by the expressions depending only on static polarizabilities. Thus, using constant ratio approximation, CRA2 [60] the first integral in eq. (9) can be written in the form…”
Section: Analytical Calculation Detailsmentioning
confidence: 99%
“…The potential can be satisfactorily estimated by a series expansion of the form where the first term represents a short-range effect related to exchange or overlap type interactions [30,31], whereas the second part of the formula, distinguished from the series expansion, is introduced to enable the long-range part of the potential to diminish according to a ∼ 1/R 6 dependence; the other far-distance contributions (including dispersion-and induction-like processes) are entangled in the final summation. The q i parameters are obtained by fitting the function to the ab initio data sets reported in Ref.…”
Section: Fitting Functionsmentioning
confidence: 99%